(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
The objective of the work was to identify the harvesting system used, its adaptations, describe the harvesting activities, characterization of the machines used and the costing. The costs raised in this work were divided by activity and cost component. The work resulted in the description of the forest felling, this being carried out using three chainsaws of the Stihl brand, model MS 660 with the chainsaw teams adjusted to the scheme (1+1), an operator and a helper. As an adaptation of the system, the extraction was performed from inside the field to the storage yard, and executed with the aid of a Massey Ferguson tractor, model MF 275 of medium size with high axle, 4x2 rear-wheel drive, 75 horsepower and torque of approximately 28 kgfm adapted with a winch and use of drag chain, a tractor driver and two assistants. Labor costs were the most expensive, representing 80.82% of the total harvest cost. Gross profit per hectare was R 15,525.00, of which 30.76% was consumed by operating costs, being labor the most significant. It is interesting in semi-mechanized harvests to add value by drying and commercializing already sawn wood. Selling raw logs, as it was performed in this work, significantly decreases the price of the cubic meter